THE EFFECT OF PERCEIVED FAIRNESS ON BURNOUT, TURNOVER INTENTION, AND JOB SATISFACTION AUDITORS (STUDY ON AUDITORS OF THE SUPREME AUDIT AGENCY OF THE REPUBLIC OF INDONESIA) - Ivan Ardian Sani (Berkala Akuntansi dan Keuangan Indonesia, 2017)
This study aims to investigate whether the interaction relationship between auditors and audit agencies has an effect on burnout, job satisfaction, and auditor turnover intention. Previous research has investigated the antecedents, consequences, and strategies to mitigate burnout, but it is still rare to investigate burnout in terms of the interaction relationship between the auditor and the organization where he works. This study provides findings that the interaction relationship between auditors and the audit agency where they work has an effect on the level of burnout experienced and also has an impact on auditor performance outputs such as turnover intention. This study also proves empirically that burnout has a negative impact on auditors because it can lead to decreased job satisfaction and increased turnover intention. This research is important because it uses a research sample of government auditors, namely BPK auditors.